HISTORY AND DEVELOPMENT OF THE UZBEK LANGUAGE (Лучшие интеллектуальные исследования, 2025)
Abstract- This article explores the historical roots and developmental stages of the Uzbek language — one of the oldest and richest Turkic languages in Central Asia. From its early Turkic origins to its modern literary form, the evolution of Uzbek has gone through significant changes under the influence of history, politics, and culture. The article also highlights the role of major figures in shaping the language and looks at recent reforms in orthography and education that continue to influence its growth.